Social Media as a Learning Tool for Tenth-Grade Akidah Akhlak Students: A Case at Madrasah Aliyah Mathla’ul Anwar Kedondong, Pesawaran, Lampung - Ali Husen, Rizkon; Fajri, M. Rizkal; Rohili, Tahir (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2026)
Islamic education plays a vital role in shaping the character and personality of students through the internalization of faith (akidah) and moral values (akhlak). Meanwhile, the rapid advancement of digital technology and social media has become increasingly prevalent among adolescents, including those in madrasah settings. However, the use of mobile phones during classroom instruction remains restricted, leaving the potential of social media as a formal learning support tool underutilized. This study aims to identify the role of social media in supporting the learning process of Akidah Akhlak for tenth-grade students at Madrasah Aliyah Mathla’ul Anwar Kedondong, Pesawaran. A qualitative descriptive-phenomenological approach was employed to obtain a comprehensive understanding of social media use as a learning tool outside of class hours. Research subjects comprised one Akidah Akhlak teacher and 62 tenth-grade students, with data collected through interviews, observation, and documentation. Findings indicate that social media plays a significant role as a communication medium between teachers and students, a supplementary learning resource, and a means of reinforcing faith and moral values. The most widely used platform was WhatsApp (100%), followed by Instagram (77.4%), TikTok (72.6%), YouTube (66.1%), and Facebook (19.4%). Appropriate utilization of social media can expand access to learning, increase student engagement, and support the formation of religious character aligned with Islamic values.